Treatment Pattern of Antidiabetic Drugs Use One Type II Diabetes Mellitus Patients at RSAU dr. M. Salamun - Dhiyah Malihah; Rida Emelia (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2022)
Diabetes mellitus is a group of metabolic diseases with characteristic of hyperglycemia that occur due to abnormalities of insulin secretion, insulin activity or both, Indonesia now ranks sixth with the highest number of diabetes after the United States, China, India, Brazil and Mexico. Based on data from the IDF Atlas in 2017, the number of diabetes in Indonesia reached 10.3 million, if not handled properly, according to the WHO the incidence of diabetes is predicted to rise to 21.3 million by 2040. This research is non-experiential observational studies were conducted using retrospective research designs to know the description of drugs use pattern and treatment pattern of antidiabetic drug use on Type II Diabetes Mellitus patiens at RSAU dr. M. Salamun in 2021. The samples were 80 medical records of patients with Type II diabetes mellitus taken in total sampling. Data presented in the form of diagram/tables and percentages. The results of this study were able to find out that the classes of oral antidiabetic durgs administered to patients were sulfonylurea 97 drugs (61.78%), biquanide 38 drugs (24.20%), alpha-glucosidase 12 drugs (7.64%), and thiazolidinedione 10 drugs (6.36%). Accuracy assessment based on the patient oral antidiabetic drug delivery are as follows: 44 patients (55%) of appropriate-drugs-doses, 69 patients (89,25%) for appropriate drug indications. Keywords: Type II Diabetes Mellitus, Treatment Pattern, RSAU dr. M. Salamun.